Antenatal diagnosis of mucopolysaccharidosis type I (Hurler's disease) is not possible by electron microscopy of uncultured amniotic fluid cells. Issue 5 (October 1984) - Hug, G; Soukup, S; Chuck, G; Ryan, M
Abstract : Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disorder characterised by the deficient activity of iduronidase and by the presence of MPS vacuoles in many tissues of affected patients. We studied whether these characteristics could be used for the antenatal diagnosis of the disease. We obtained amniotic fluid cells from two pregnancies at risk for MPS I, one pregnancy at risk for GSD II (another lysosomal disease), and eight normal control pregnancies. Measurements of iduronidase activity in cultured amniotic fluid cells indicated the presence of a MPS I fetus in one high risk pregnancy and an unaffected fetus in the other. This diagnosis was confirmed at delivery. On electron microscopy the uncultured amniotic fluid cells exhibited MPS-like vacuoles in the pregnancy with a GSD II fetus, in three of eight normal pregnancies, and in the pregnancy at risk for MPS I that had a normal fetus. No such vacuoles were seen in the pregnancy with the MPS I fetus. These false positive and false negative findings indicate that antenatal diagnosis of MPS I cannot be based on the electron microscopic presence or absence of MPS I vacuoles in uncultured amniotic fluid cells.